Leaf manganese concentrations as a tool to assess belowground plant functioning in phosphorus-impoverished environments - Lambers, Hans; Wright, Ian J.; Pereira, Caio Guilherme; Bellingham, Peter J.; Bentley, Lisa Patrick; Boonman, Alex; Cernusak, Lucas A.; Foulds, William; Gleason, Sean M.; Gray, Emma F.; Hayes, Patrick E.; Kooyman, Robert M.; et al. (Plant and soil, 2021)
Background and aims Root-released carboxylates enhance the availability of manganese (Mn), which enters roots through transporters with low substrate specificity. Leaf Mn concentration ([Mn]) has been proposed as a signature for phosphorus (P)-mobilising carboxylates in the rhizosphere. Here we test whether leaf [Mn] provides a signature for root functional types related to P acquisition. Methods Across 727 species at 66 sites in Australia and New Zealand, we measured leaf [Mn] as related to root functional type, while also considering soil and climate variables. To further assess the specific situations under which leaf [Mn] is a suitable proxy for rhizosphere carboxylate concentration, we studied leaf [Mn] along a strong gradient in water availability on one representative site. In addition, we focused on two systems where a species produced unexpected results. Results Controlling for background site-specific variation in leaf [Mn] with soil pH and mean annual precipitation, we established that mycorrhizal species have significantly lower leaf [Mn] than non-mycorrhizal species with carboxylate-releasing root structures, e.g., cluster roots. In exception to the general tendency, leaf [Mn] did not provide information about root functional types under seasonally waterlogged conditions, which increase iron availability and thereby interfere with Mn-uptake capacity. Two further exceptions were scrutinised, leading to the conclusion that they were ‘anomalous’ in not functioning like typical species in their families, as expected according to the literature. Conclusions Leaf [Mn] variation provides considerable insights on differences in belowground functioning among co-occurring species. Using this approach, we concluded that, within typical mycorrhizal families, some species actually depend on a carboxylate-releasing P-mobilising strategy. Likewise, within families that are known to produce carboxylate-releasing cluster roots, some do not produce functional cluster roots when mature. An analysis of leaf [Mn] can alert us to such ‘anomalous’ species.